Australian mental health care practitioners' practices and attitudes for encouraging smoking cessation and tobacco harm reduction in smokers with severe mental illness. (3rd February 2017) - Sharma, Ratika; Meurk, Carla; Bell, Stephanie; Ford, Pauline; Gartner, Coral
Abstract: Reducing the burden of physical illness among people living with severe mental illnesses (SMI) is a key priority. Smoking is strongly associated with SMIs resulting in excessive smoking related morbidity and mortality in smokers with SMI. Smoking cessation advice and assistance from mental health practitioners would assist with reducing smoking and smoking‐related harms in this group. This study examined the attitudes and practices of Australian mental health practitioners towards smoking cessation and tobacco harm reduction for smokers with SMI, including adherence to the 5As (ask, assess, advise, assist and arrange follow up) of smoking cessation. We surveyed 267 Australian mental health practitioners using a cross‐sectional, online survey. Most practitioners (77.5%) asked their clients about smoking and provided health education (66.7%) but fewer provided direct assistance (31.1–39.7%). Most believed that tobacco harm reduction strategies are effective for reducing smoking related risks (88.4%) and that abstinence from all nicotine should not be the only goal discussed with smokers with SMI (77.9%). Many respondents were unsure about the safety (56.9%) and efficacy (39.3%) of e‐cigarettes. Practitioners trained in smoking cessation were more likely (OR: 2.9, CI: 1.5–5.9) to help their clients to stop smoking. Community mental health practitioners (OR: 0.3, CI: 0.1–0.9) and practitioners who were current smokers (OR: 0.3, CI: 0.1–0.9) were less likely to adhere to the 5As of smoking cessation intervention. The results of this study emphasize the importance and need for providing smoking cessation training to mental health practitioners especially community mental health practitioners.